Within the Web: The Family/Practitioner Relationship in the Context of Chronic Childhood Illness - Dickinson, Annette R (Auckland University of Technology, 2004)
This study explores the phenomenon of the relationships between practitioners and families who have a child with a chronic illness. Using a heremeneutic phenomenological method informed by the writings of Martin Heidegger [1889-1976] and Hans-Georg Gadamer [1900-2002], this study provides an understanding of the meaning of 'being in relationship' from the perspective of both families and practitioners.Study participants include ten family groups who have a child with a chronic illness and twelve practitioners from the disciplines of nursing, medicine, dietetics, physiotherapy and speech therapy who work with children with chronic illness. Narrative audiotaped interviewing was the means by which the participants told their stories about times that relationships worked well and when they did not. These stories uncover the every day realities of 'being in relationship' and provide another understanding of the relationship between family and practitioner.The findings of this thesis suggest that chronic childhood illness 'throws' families and practitioners together into a web of relationships that must work for the sake of the child. The relationship is primarily conducted between adults. Children are usually excluded. In order to understand and manage the child's illness, practitioners and families 'go around' and act 'in-between' relationships. While the quality of the relationship from the family perspective is not essential to the chronic illness journey, relationships are more successful when practitioners recognise the uniqueness of each family web. The nature of the relationship is often simple, yet it co-exists with complexity. This thesis proposes that a 'companion relationship' between practitioners and family may offer a more effective and satisfying way of working. It also challenges practitioners to consider the voice of children within health care relationships.
Keywords: Chronic diseases in children; Parent and child; Family; Professional-Family Relations; Chronic Disease; Child; Health Studies